1998
DOI: 10.1007/s004050050067
|View full text |Cite
|
Sign up to set email alerts
|

Osteolipoma in the parapharyngeal space

Abstract: We report our experience in managing a 58-year-old Japanese woman with a rare parapharyngeal interstitial cell tumor. Her main complaint was that of a submandibular swelling, which was diagnosed as osteolipoma histologically after resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 10 publications
1
36
0
Order By: Relevance
“…Only four cases of this rare type of lipoma presented as neck masses [4,11], two of which reported in 1973 and 1998 in the submandibular area [12,13]. We are reporting the third case in this special location.…”
Section: Introductionmentioning
confidence: 87%
“…Only four cases of this rare type of lipoma presented as neck masses [4,11], two of which reported in 1973 and 1998 in the submandibular area [12,13]. We are reporting the third case in this special location.…”
Section: Introductionmentioning
confidence: 87%
“…Under normal conditions, the existence of adipose tissue in some regions can explain the occurrence of a lipoma and subsequent osteolipoma (9). Ohno et al stated that fibrous tissue is the origin for bone changes in a lipoma (3). It is still controversial whether this disorder is a hamartoma, a neoplasm, or metaplastic.…”
Section: Discussionmentioning
confidence: 99%
“…Allen et al reported that only 6 of 635 cases with benign lipomas in their study showed ossification (2). Clinically, an osteolipoma, containing mature lamellar bones irregularly arranged in a significant fat component, is quite rare (3,4). In contrast, an ossifying lipoma usually occurs within the intrathecal bone and rarely within the cortical bone.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the English literature found that, outside the head and neck area, lipomas with osseous differentiation have been reported in deep locations adjacent to bone tissue in the thigh [10][11][12][13], knee [14,15], sternoclavicular region [16], shoulder [17], wrist [14], hand [18], intraspinal [19] or in superficial subcutaneous tissue [20,21]. More than 60 % of the cases occur in the head and neck region, where they have been described in intraspinal [22], intracranial [23] (suprasellar/hypothalamic and interhemispheric) and extracranial-extraspinal locations [3][4][5][6][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The latter are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Admixed differentiation into a diversity of mesenchymal elements, such as fibrous tissue (fibrolipoma), blood vessels (angiolipoma) or muscle (myolipoma) is a relatively frequent event. Osseous change is extremely rare, mainly in large and long-standing lipomas [5,6]. We report our experience in managing a patient with a submandibular mass with the configuration of a lipoma and with concurrent bone and cartilaginous differentiation, consistent with an osteochondrolipoma.…”
Section: Introductionmentioning
confidence: 95%